[18F]Fluorine-Labeled Pharmaceuticals: Direct Aromatic Fluorination Compared to Multi-Step Strategies - Krüll, Jasmin; Heinrich, Markus (Asian Journal of Organic Chemistry, 2019)
Positron emission tomography (PET) presents an important tool for medicinal and pharmaceutical investigations, with applications ranging from fundamental research to the diagnosis of a broad variety of diseases. Crucial for the use of this technique is, however, a robust labeling strategy for the preparation of the required radiolabeled compound. For 18-fluorine-labeling, which represents the most widely applied method in this field, it is interesting to note that a kind of paradigm change occurred over the last years. While multi-step labeling strategies were the preferred approach for many decades, mainly due to the lack of suitable leaving groups for direct [ 18 F]fluorination reactions, the synthetic tools to achieve the highly attractive direct 18-fluorine-labeling rapidly increased recently. This focus review points out a comparison between the multi-step approaches and the newly developed direct fluorination strategies available for nucleophilic 18-fluorination of carbocyclic aromatic systems, including a discussion of advantages and limitations.
CRIS-Team Scopus Importer:2019-05-28
Keywords: 18-fluorine; fluorination; PET; radiolabeling; radiopharmaceuticals

[18F]Fluorophenylazocarboxylates: Design and Synthesis of Potential Radioligands for Dopamine D3 and μ‑Opioid Receptor. - Nebel, Natascha; Strauch, Brigitte; Maschauer, Simone; Lasch, Roman; Rampp, Hannelore; Fehler, Stefanie; Bock, Leonard; Hübner, Harald; Gmeiner, Peter; Heinrich, Markus; Prante, Olaf (ACS Omega, 2017)
18F-Labeled building blocks from the type of [18F]fluorophenylazocarboxylic-tert-butyl esters offer a rapid, mild, and reliable method for the 18F-fluoroarylation of biomolecules. Two series of azocarboxamides were synthesized as potential radioligands for dopamine D3 and the μ-opioid receptor, revealing compounds 3d and 3e with single-digit and sub-nanomolar affinity for the D3 receptor and compound 4c with only micromolar affinity for the μ-opioid receptor, but enhanced selectivity for the μ-subtype in comparison to the lead compound AH-7921. A "minimalist procedure" without the use of a cryptand and base for the preparation of 4-[18F]fluorophenylazocarboxylic-tert-butyl ester [ 18 F]2a was established, together with the radiosynthesis of methyl-, methoxy-, and phenyl-substituted derivatives ([ 18 F]2b-f). With the substituted [18F]fluorophenylazocarbylates in hand, two prototype azocarboxylates radioligands were synthesized by 18F-fluoroarylation, namely the methoxy azocarboxamide [ 18 F]3d as the D3 receptor radioligand and [ 18 F]4a as a prototype structure of the μ-opioid receptor radioligand. By introducing the new series of [18F]fluorophenylazocarboxylic-tert-butyl esters, the method of 18F-fluoroarylation was significantly expanded, thereby demonstrating the versatility of 18F-labeled phenylazocarboxylates for the design of potential radiotracers for positron emission tomography .
EVALuna2:34730

2-Fluoro-5-nitrophenyldiazonium: A Novel Sanger-Type Reagent for the Versatile Functionalization of Alcohols - Fischer, Oliver; Heinrich, Markus (Chemistry - A European Journal, 2021)
As a novel Sanger-type reagent, 2-fluoro-5-nitrophenyldiazonium tetrafluoroborate enabled the versatile functionalization of primary and secondary aliphatic alcohols. Based on a mild nucleophilic aromatic substitution of the fluorine atom under unprecedented, base-free conditions, the diazonium unit on the aromatic core of the resulting aryl-alkyl ether could be employed for such diverse transformations as radical C−H activation and cyclization, as well as palladium catalyzed cross-coupling reactions.
CRIS-Team Scopus Importer:2021-03-05
Keywords: C−C bond formation; C−H activation; diazonium; nucleophilic aromatic substitution; Sanger reagent

4-substituted tert-butyl phenylazocarboxylates-synthetic equivalents for the para-phenyl radical cation - Höfling, Sarah; Bartuschat, Amelie; Heinrich, Markus (Angewandte Chemie International Edition, 2010)
First electrophile, then radical: 4-Substituted tert-butyl phenylazocarboxylates 1 are versatile synthetic equivalents of the para-phenyl radical cation 2. The tert-butyloxycarbonylazo group enables nucleophilic substitutions to proceed under mild conditions and can later be employed for the generation of aryl radicals. Copyright © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: arenes; aromatic substitution; nucleophilic substitution; radical reactions; synthetic methods

A Metabolomic Analysis of Sensitivity and Specificity of 23 Previously Proposed Biomarkers for Renal Transporter-Mediated Drug-Drug Interactions - Geßner, Arne; Müller, Fabian; Wenisch, Pia; Heinrich, Markus; König, Jörg; Stopfer, Peter; Fromm, Martin (Clinical Pharmacology & Therapeutics, 2023)
Endogenous biomarkers are discussed as tools for detection of drug-drug interactions (DDIs) mediated by renal transport proteins, such as organic cation transporter 2 (OCT2), multidrug and toxin extrusion proteins (MATE1 and MATE2-K) and organic anion transporters (OAT1 and OAT3). Whereas sensitivity of some endogenous biomarkers against at least one clinical transporter inhibitor has frequently been shown, intra-study comparisons of the extent of effects of inhibitors on different biomarkers are frequently lacking. Moreover, in vivo specificity of such discussed biomarkers has frequently not been studied. We therefore investigated changes of 10 previously described putative biomarkers for inhibition of OCT2/MATEs, as well as 15 previously described putative biomarkers for OATs in human plasma and urine samples of healthy volunteers in response to treatment with 4 inhibitors of transport proteins [verapamil (P-glycoprotein), rifampin (organic anion transporting polypeptides), cimetidine (OCT2/MATEs), and probenecid (OATs)]. Two of the putative biomarkers had been suggested for both OCT2/MATEs and OATs. All substances were unequivocally identified in an untargeted metabolomics assay. The OCT2/MATE biomarkers choline and trimethylamine N-oxide were both sensitive and specific (median log2-fold changes −1.18 in estimated renal elimination and −0.85 in urinary excretion, respectively). For renal OATs, indoleacetyl glutamine and indoleacetic acid (median log2-fold changes −3.77 and −2.85 in estimated renal elimination, respectively) were the candidates for sensitive and specific biomarkers with the most extensive change, followed by taurine, indolelactic acid, and hypoxanthine. This comprehensive study adds further knowledge on sensitivity and specificity of 23 previously described biomarkers of renal OCT2/MATE- and OAT-mediated DDIs.
CRIS-Team Scopus Importer:2023-10-27

Analysis of hyperforin (St. John’s wort) action at TRPC6 channel leads to the development of a new class of antidepressant drugs - El Hamdaoui, Yamina; Zheng, Fang; Fritz, Nikolas; Ye, Lian; Tran, Mai Anh; Schwickert, Kevin; Schirmeister, Tanja; Braeuning, Albert; Lichtenstein, Dajana; Hellmich, Ute A.; Weikert, Dorothée; Heinrich, Markus; et al. (Molecular Psychiatry, 2022)
St. John’s wort is an herb, long used in folk medicine for the treatment of mild depression. Its antidepressant constituent, hyperforin, has properties such as chemical instability and induction of drug-drug interactions that preclude its use for individual pharmacotherapies. Here we identify the transient receptor potential canonical 6 channel (TRPC6) as a druggable target to control anxious and depressive behavior and as a requirement for hyperforin antidepressant action. We demonstrate that TRPC6 deficiency in mice not only results in anxious and depressive behavior, but also reduces excitability of hippocampal CA1 pyramidal neurons and dentate gyrus granule cells. Using electrophysiology and targeted mutagenesis, we show that hyperforin activates the channel via a specific binding motif at TRPC6. We performed an analysis of hyperforin action to develop a new antidepressant drug that uses the same TRPC6 target mechanism for its antidepressant action. We synthesized the hyperforin analog Hyp13, which shows similar binding to TRPC6 and recapitulates TRPC6-dependent anxiolytic and antidepressant effects in mice. Hyp13 does not activate pregnan-X-receptor (PXR) and thereby loses the potential to induce drug-drug interactions. This may provide a new approach to develop better treatments for depression, since depression remains one of the most treatment-resistant mental disorders, warranting the development of effective drugs based on naturally occurring compounds.
CRIS-Team Scopus Importer:2022-10-21

An untargeted metabolomics approach to evaluate enzymatically deconjugated steroids and intact steroid conjugates in urine as diagnostic biomarkers for adrenal tumors - Vogg, Nora; North, Eleanor; Geßner, Arne; Fels, Felix; Heinrich, Markus; Kroiss, Matthias; Kurlbaum, Max; Fassnacht, Martin; Fromm, Martin (Clinical Chemistry and Laboratory Medicine, 2025)
Objectives: Urinary steroid profiling after hydrolysis of conjugates is an emerging tool to differentiate aggressive adrenocortical carcinomas (ACC) from benign adrenocortical adenomas (ACA). However, the shortcomings of deconjugation are the lack of standardized and fully validated hydrolysis protocols and the loss of information about the originally conjugated form of the steroids. This study aimed to evaluate the quality of the deconjugation process and investigate novel diagnostic biomarkers in urine without enzymatic hydrolysis. Methods: 24 h urine samples from 40 patients with ACC and 40 patients with ACA were analyzed by untargeted metabolomics using liquid chromatography-high-resolution mass spectrometry both unmodified and after hydrolysis with arylsulfatase/glucuronidase from Helix pomatia. Both approaches were compared regarding the differentiation of ACC vs. ACA via ROC analyses and to evaluate the hydrolyzation efficiency of steroid conjugates. Results: Steroid glucuronides were fully deconjugated, while some disulfates and all monosulfates were still largely detectable after enzymatic hydrolysis, suggesting incomplete and variable deconjugation. In unhydrolyzed urine, steroid monosulfates showed the best differentiation between ACC and ACA (highest AUC=0.983 for C21H32O6S, followed by its isomer and two isomers with the molecular formula C21H32O7S). Moreover, several disulfates were highly abundant and increased in ACC compared to ACA. Conclusions: This work highlights the limitations of hydrolyzing steroid conjugates before analysis and shows a possible superiority of a direct analysis approach compared to a hydrolysis approach from a methodological point of view and regarding diagnostic accuracy. Several steroid conjugates were found as promising diagnostic biomarkers for differentiation between ACC and ACA.
CRIS-Team Scopus Importer:2025-01-31
Keywords: adrenocortical adenoma; adrenocortical carcinoma; conjugated steroids; enzymatic hydrolysis; LC-MS; mass spectrometry

Aryl Radical Selectivity in Biphasic Systems - Altmann, Lisa-Marie; Fürst, Michael; Gans, Eva; Zantop, Viviane; Pratsch, Gerald; Heinrich, Markus (Organic Letters, 2020)
Aryl radicals generated in the aqueous phase of biphasic mixtures have-regardless of a comparably low polarity- A strong preference to react with aromatic substrates in the aqueous phase and not to undergo phase-transfer into a lipophilic phase, independent from the presence of a surfactant. These results represent an important prerequisite toward future studies in biological systems, which typically consist of various compartments of either hydrophilic or lipophilic character.
CRIS-Team Scopus Importer:2020-02-04

Base-Induced Radical Carboamination of Nonactivated Alkenes with Aryldiazonium Salts - Kindt, Stephanie; Wicht, Karina; Heinrich, Markus (Organic Letters, 2015)
A new transition-metal-free version of the Meerwein arylation has been developed. The key feature of this carboamination-type reaction is the slow base-controlled generation of aryl radicals from aryldiazonium tetrafluoroborates, so that a sufficient quantity of diazonium ions remains to enable efficient trapping of the alkyl radical adduct resulting from aryl radical addition to the alkene. Under strongly basic conditions, diazoanhydrides are likely to take over the role of the nitrogen-centered radical scavengers.

Behavioural effects of APH199, a selective dopamine D4 receptor agonist, in animal models - Chestnykh, Daria; Graßl, Fabian; Pfeifer, Conrad; Dülk, Jonas; Ebner, Chiara; Walters, Mona; von Hörsten, Stephan; Kornhuber, Johannes; Kalinichenko, Liubov; Heinrich, Markus; Müller, Christian P. (Psychopharmacology, 2023)
Rationale: The dopamine D4 receptors (DRD4) play a key role in numerous brain functions and are involved in the pathogenesis of various psychiatric disorders. DRD4 ligands have been shown to moderate anxiety, reward and depression-like behaviours, and cognitive impairments. Despite a series of promising but ambiguous findings, the therapeutic advantages of DRD4 stimulation remain elusive. Objectives: The investigation focused on the behavioural effects of the recently developed DRD4 agonist, APH199, to evaluate its impact on anxiety, anhedonia, behavioural despair, establishment and retrieval of alcohol reinforcement, and amphetamine (AMPH)-induced symptoms. Methods: Male C57BL/6 J mice and Sprague–Dawley rats were examined in five independent experiments. We assessed APH199 (0.1–5 mg/kg, i.p.) effects on a broad range of behavioural parameters in the open field (OF) test, conditioned place preference test (CPP), elevated plus maze (EPM), light–dark box (LDB), novelty suppressed feeding (NSF), forced swim test (FST), sucrose preference test (SPT), AMPH-induced hyperlocomotion test (AIH), and prepulse inhibition (PPI) of the acoustic startle response in AMPH-sensitized rats. Results: APH199 caused mild and sporadic anxiolytic and antidepressant effects in EPM and FST, but no remarkable impact on behaviour in other tests in mice. However, we found a significant increase in AMPH-induced hyperactivity, suggesting an exaggeration of the psychotic-like responses in the AMPH-sensitized rats. Conclusions: Our data challenged the hypothesis of the therapeutic benefits of DRD4 agonists, pointing out a possible aggravation of psychosis. We suggest a need for further preclinical studies to ensure the safety of antipsychotics with DRD4 stimulating properties.
CRIS-Team Scopus Importer:2023-03-10
Keywords: Alcohol; Anxiety; APH199; Depression; DRD4 agonist; Psychosis; Schizophrenia

Benzyl Phenylsemicarbazides: A Chemistry-Driven Approach Leading to G Protein-Biased Dopamine D4 Receptor Agonists with High Subtype Selectivity - Pirzer, Anna; Lasch, Roman; Friedrich, Heike; Hübner, Harald; Gmeiner, Peter; Heinrich, Markus (Journal of Medicinal Chemistry, 2019)
Many subtype-selective dopamine receptor ligands developed for the D2-D4 family incorporate a 1-arylpiperazine-derived primary recognition motif, which is connected to a lipophilic moiety occupying an extended binding pocket (EBP) of the receptor via an aliphatic linker of variable lengths. The evaluation of a novel group of dopamine receptor ligands now showed that highly subtype-selective ligands [up to Ki(D4.4) = 0.25 nM, D2L/D4.4 = 320, D3/D4.4 = 710 for APH199 (17)] can be obtained by choosing a relatively large and conformationally flexible 1-benzyl-1-phenylsemicarbazide substructure to fill the EBP. The novel chemotype APH199 (17) was found to act as a full agonist at the D4 receptor showing significant bias toward G protein activation over β-arrestin recruitment in comparison to quinpirole.
CRIS-Team Scopus Importer:2019-11-15

Characterization of Fluorescent Dyes Frequently Used for Bioimaging: Photophysics and Photocatalytical Reactions with Proteins - Archipowa, Nataliya; Wittmann, Lukas; Köckenberger, Johannes; Ertl, Fabian J.; Gleixner, Jakob; Keller, Max; Heinrich, Markus; Kutta, Roger Jan (Journal of Physical Chemistry B, 2023)
Derivatives of the rhodamine-based dye 5-TAMRA (5-carboxy-tetramethylrhodamine) and the indocarbocyanine-type Cy3B (cyclized derivative of the cyanine dye Cy3), both representing important fluorophores frequently used for the labeling of biomolecules (proteins, nucleic acids) and bioactive compounds, such as receptor ligands, were photophysically investigated in aqueous solution, i.e., in neat phosphate-buffered saline (PBS) and in PBS supplemented with 1 wt % bovine serum albumin (BSA). The dyes exhibit comparable absorption (λabs,max: 550-569 nm) and emission wavelengths (λem,max: 580-582 nm), and similar S1 lifetimes (2.27-2.75 ns), and their excited state deactivation proceeds mainly via the lowest excited singlet state (triplet quantum yield ca. 1%). However, the probes show marked differences with respect to their fluorescence quantum yield and photostability. While 5-TAMRA shows a lower quantum yield (37-39%) than the Cy3B derivative (ca. 57%), its photostability is considerably higher compared to Cy3B. Generally, the impact of the protein on the photophysics is low. However, on prolonged illumination, both fluorescent dyes undergo a photocatalytic reaction with tryptophan residues of BSA mediated by sensitized singlet oxygen resulting in a tryptophan photoproduct with an absorption maximum around 330 nm. The overall results of this work will assist in choosing the right dye for the labeling of bioactive compounds, and the study demonstrates that experiments performed with 5-TAMRA or Cy3B-labeled compounds in a biological environment may be influenced by photochemical modification of experimentally relevant proteins at aromatic amino acid residues.
CRIS-Team Scopus Importer:2023-11-24

Cleavage of Organosolv Lignin to Phenols Using Nitrogen Monoxide and Hydrazine - Hofmann, Laura; Altmann, Lisa-Marie; Fischer, Oliver; Prusko, Lea; Xiao, Ganyuan; Westwood, Nicholas J.; Heinrich, Markus (ACS Omega, 2021)
From the variety of methods known for the depolymerization of organosolv lignin, a broad range of diversely substituted aromatic compounds are available today. In the present work, a novel two-step reaction sequence is reported, which is focused on the formation of phenols. While the first step of the depolymerization strategy comprises the 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ)-catalyzed oxidation of organosolv lignin with nitrogen monoxide so that two waste materials are combined, cleavage to the phenolic target compounds is achieved in the second step employing hydrazine and potassium hydroxide under Wolff-Kishner-type conditions. Besides the fact that the novel strategy proceeds via an untypical form of oxidized organosolv lignin, the two-step sequence is further able to provide phenols as cleavage products, which bear no substituent at the 4-position.
CRIS-Team Scopus Importer:2021-09-03

Connecting Ruthenium Photocatalysis to 1,2-Dioxetane-Mediated Chemiluminescence: a Versatile Combination for Optical Detection and Read-Out - Köckenberger, Johannes; Thurston, Ryan; Sauer, Caroline; Oppl, Janina; Heinrich, Markus (Angewandte Chemie International Edition, 2023)
Optical storage and photon quantification systems based on sensitive photoreactions have numerous applications. Herein, we report a highly efficient photocatalytic reaction, in which ruthenium photoredox catalysis is combined with a 1,2-dioxetane from which chemiluminescence can be triggered. In this system, blue light irradiation as optical input enables a defined inverse correlation with base-triggered, blue light emission as optical output. Comparison of readout by 1H NMR and chemiluminescence, relative to previous optical input, underlines the reliability and usefulness of the ruthenium-dioxetane system for optical storage, sensing and ruthenium detection.
CRIS-Team Scopus Importer:2023-07-07
Keywords: 1; 2-Dioxetanes; Actinometry; CIEEL; Optical Storage; Photocatalysis

Current Advances in Meerwein-type Radical Alkene Functionalizations - Diesendorf, Nina; Heinrich, Markus (Synthesis (Germany), 2022)
Alkene functionalizations via Meerwein arylations are becoming increasingly attractive, especially since a variety of mild and sustainable methods for aryl radical generation are available today. This entails a broad spectrum of substrates and radical scavengers, as well as convenient synthetic routes to relevant precursors for further transformations. The present review focuses on recent advances in Meerweintype alkene functionalizations and gives insights into the key mechanistic details of the respective reactions. 1 Introduction 2 Hydroarylation and Carboarylation 3 Carboamination, Carbooxygenation, and Carbothiolation 4 Carbohalogenation 5 Conclusion and Outlook
CRIS-Team Scopus Importer:2022-03-18
Keywords: Meerwein arylation; olefins; photocatalysis; radical chemistry; radical-polar crossover

Cyanine- and Rhodamine-Derived Alkynes for the Selective Targeting of Cancerous Mitochondria through Radical Thiol-Yne Coupling in Live Cells - Köckenberger, Johannes; Klemt, Insa; Sauer, Caroline; Arkhypov, Anton; Reshetnikov, Viktor; Mokhir, Andriy; Heinrich, Markus (Chemistry - A European Journal, 2023)
Despite their long history and their synthetic potential underlined by various recent advances, radical thiol-yne coupling reactions have so far only rarely been exploited for the functionalization of biomolecules, and no examples yet exist for their application in live cells - although natural thiols show widespread occurrence therein. By taking advantage of the particular cellular conditions of mitochondria in cancer cells, we have demonstrated that radical thiol-yne coupling represents a powerful reaction principle for the selective targeting of these organelles. Within our studies, fluorescently labeled reactive alkyne probes were investigated, for which the fluorescent moiety was chosen to enable both mitochondria accumulation as well as highly sensitive detection. After preliminary studies under cell-free conditions, the most promising alkyne-dye conjugates were evaluated in various cellular experiments comprising analysis by flow cytometry and microscopy. All in all, these results pave the way for improved future therapeutic strategies relying on live-cell compatibility and selectivity among cellular compartments.
CRIS-Team Scopus Importer:2023-06-30
Keywords: alkynes; mitochondria; radicals; selective targeting; thiols

Cycloaddition reactions of glycine imine anions to phenylazocarboxylic esters - A new access to 1,3,5-trisubstituted 1,2,4-triazoles - Lasch, Roman; Heinrich, Markus (Tetrahedron, 2015)
Phenylazocarboxylic tert-butyl esters have recently been shown to be highly versatile building blocks due to their ability to undergo nucleophilic aromatic substitutions under mild conditions, particularly well with [18F]fluoride, and to act as precursors for aryl radicals. In this article, we now report first examples for cycloaddition reactions to phenylazocarboxylates. In a one-pot reaction with readily accessible glycine imines, a variety of highly substituted 1,2,4-triazoles could be obtained.
Keywords: 1; 2; 4-Triazoles; Azo compounds; Azocarboxylic esters; Cycloaddition; Glycine imines

Development of Photoactivatable Allosteric Modulators for the Chemokine Receptor CXCR3 - Admas, Tizita; Bernat, Viachaslau; Heinrich, Markus; Tschammer, Nuska (ChemMedChem, 2016)
The CXCR3 receptor, a class A G protein-coupled receptor (GPCR), is involved in the regulation and trafficking of various immune cells. CXCR3 antagonists have been proposed to be beneficial for the treatment of a wide range of disorders including but not limited to inflammatory and autoimmune diseases. The structure-based design of CXCR3 ligands remains, however, hampered by a lack of structural information describing in detail the interactions between an allosteric ligand and the receptor. We designed and synthesized photoactivatable probes for the structural and functional characterization, using photoaffinity labeling followed by mass spectrometry, of the CXCR3 allosteric binding pocket of AMG 487 and RAMX3, two potent and selective CXCR3 negative allosteric modulators. Photoaffinity labeling is a common approach to elucidate binding modes of small-molecule ligands of GPCRs through the aid of photoactivatable probes that convert to extremely reactive intermediates upon photolysis. The photolabile probe N-[(1-[3-(4-ethoxyphenyl)-4-oxo-3,4-dihydropyrido[2,3-d]pyrimidin-2-yl]ethyl-2-[4-fluoro-3-(trifluoromethyl)phenyl]-N-1-[4-(3-(trifluoromethyl)-3H-diazirin-3-yl]benzylpiperidin-4-yl)methyl]acetamide (10) showed significant labeling of the CXCR3 receptor (80 %) in a [H]RAMX3 radioligand displacement assay. Compound 10 will serve as an important tool compound for the detailed investigation of the binding pocket of CXCR3 by mass spectrometry. A series of photoactivatable ligands was designed for labelling the allosteric pocket of the CXCR3 receptor, a class A G protein-coupled receptor involved in the regulation and trafficking of immune cells and thus a potential target for the treatment of inflammatory and autoimmune diseases. Compound 10 (pictured) bearing a 3-trifluoromethyl-3-phenyldiazirine group was identified as a promising tool for the study of the CXCR3 allosteric binding pocket.
Keywords: chemokine receptors; CXCR3; irreversible binding; photoactivatable ligands; photoaffinity labelling

Dually Labeled Neurotensin NTS1R Ligands for Probing Radiochemical and Fluorescence-Based Binding Assays - Ertl, Fabian J.; Kopanchuk, Sergei; Dijon, Nicola C.; Veikšina, Santa; Tahk, Maris Johanna; Laasfeld, Tõnis; Schettler, Franziska; Gattor, Albert O.; Hübner, Harald; Archipowa, Nataliya; Köckenberger, Johannes; Heinrich, Markus; et al. (Journal of Medicinal Chemistry, 2024)
The determination of ligand-receptor binding affinities plays a key role in the development process of pharmaceuticals. While the classical radiochemical binding assay uses radioligands, fluorescence-based binding assays require fluorescent probes. Usually, radio- and fluorescence-labeled ligands are dissimilar in terms of structure and bioactivity, and can be used in either radiochemical or fluorescence-based assays. Aiming for a close comparison of both assay types, we synthesized tritiated fluorescent neurotensin receptor ligands ([3H]13, [3H]18) and their nontritiated analogues (13, 18). The labeled probes were studied in radiochemical and fluorescence-based (high-content imaging, flow cytometry, fluorescence anisotropy) binding assays. Equilibrium saturation binding yielded well-comparable ligand-receptor affinities, indicating that all these setups can be used for the screening of new drugs. In contrast, discrepancies were found in the kinetic behavior of the probes, which can be attributed to technical differences of the methods and require further studies with respect to the elucidation of the underlying mechanisms.
CRIS-Team Scopus Importer:2024-09-20

Electrophotographic 3D printing of pharmaceutical films - Kopp, Sebastian-Paul; Medvedev, Vadim; Tangermann-Gerk, Katja; Wöltinger, Natalie; Rothfelder, Richard; Graßl, Fabian; Heinrich, Markus; Januskaite, Patricija; Goyanes, Alvaro; Basit, Abdul W.; Roth, Stephan; Schmidt, Michael (Additive Manufacturing, 2023)
The usage of three-dimensional (3D) printing in pharmaceutical applications offers significant advantages compared to conventional manufacturing approaches such as tableting or encapsulation. Laser sintering (LS), also referred to as powder bed fusion – laser beam (PBF-LB), formerly also known as selective laser sintering (SLS), offers the production of pharmaceuticals directly from a powder mixture with high geometrical flexibility and adjustable release profiles. However, due to limitations of conventional powder application methods for PBF-LB, neither the material composition nor the material distribution can be tailored within a printed layer. To overcome these restrictions, electrophotographic powder application (EPA), a novel method for selective powder application, was utilized in this study. EPA allows the deposited layer thickness to be reduced to values between 12 and 76 µm, depending on the used pharmaceutical powder blend. Thus, the laser energy input required for interlayer connection can be reduced, enabling the use of a CO2 laser. In this study, for the first time, EPA in combination with powder bed fusion – laser beam of polymers (EPA-PBF-LB/P) was utilized to successfully deposit and print three different model drugs: paracetamol, nicotinamide, and caffeine, mixed with Eudragit L 100–55, a pharmaceutical grade polymer. Through the use of EPA, thin layers of powder blends were successfully deposited in the build chamber, leading to no thermal degradation of the polymer or drugs from the use of a CO2 laser. Single- and multi-material pharmaceutical films were successfully printed via EPA-PBF-LB, utilizing EPA to selectively as well as precisely apply different powders within a single layer into the build chamber. This introduces a novel method of printing pharmaceuticals using SLS with a CO2 laser and without the use of additional colorants.<br
Keywords: Additive manufacturing; Electrophotography; Printed pharmaceuticals; Laser powder bed fusion; Laser sintering; Multi-material printing

Enzymatically Formed Fatty Acid Hydroperoxides Determined Through GC-MS Analysis of Enantiomeric Excess of Hydroxy Fatty Acids After Reduction and Ibuprofen Derivatization - Hotz, Lisa; Zartmann, Anne; Noack, Isabelle; Drees, Luca Janik; Kuschow, Meret; Heinrich, Markus; Janssen, Hans Gerd; Hammann, Simon (European Journal of Lipid Science and Technology, 2025)
Unsaturated fatty acids are susceptible to lipid oxidation through autoxidation, photooxygenation or enzymatical oxidation. A characteristic feature of enzyme-catalyzed oxidation is the high regio- and stereospecificity of the formed fatty acid hydroperoxides. In this study, we present a method to quantify enzymatic lipid oxidation through reducing hydroperoxy fatty acid methyl esters to hydroxy fatty acid methyl esters and derivatizing them with enantiopure (S)-ibuprofen, allowing the resolution of the enantiomer pairs as diastereomers via achiral GC-MS. After application to enantiopure reference fatty acids, the approach was applied to autoxidation products of linoleic acid, and the expected racemic mixtures of the 9- and 13-hydroperoxide derived hydroxy fatty acids were detected. On the other hand, when linoleic acid was oxidized using soybean lipoxygenase, clear enantiomeric excess of the (13S) enantiomer could be detected, proving the applicability of this method to detect enzymatic oxidation through enantiomeric excess.
CRIS-Team Scopus Importer:2025-01-31
Keywords: enantiomeric excess; gas chromatography; hydroperoxide; ibuprofen; lipid oxidation

Exploring Structural Determinants of Bias among D4 Subtype-Selective Dopamine Receptor Agonists - Graßl, Fabian; Bock, Leonard; Huete-Huerta González, Álvaro; Schiller, Martin; Gmeiner, Peter; König, Jörg; Fromm, Martin; Hübner, Harald; Heinrich, Markus (Journal of Medicinal Chemistry, 2023)
The high affinity dopamine D4 receptor ligand APH199 and derivatives thereof exhibit bias toward the Gi signaling pathway over β-arrestin recruitment compared to quinpirole. Based on APH199, two novel groups of D4 subtype selective ligands were designed and evaluated, in which the original benzyl phenylsemicarbazide substructure was replaced by either a biphenylmethyl urea or a biphenyl urea moiety. Functional assays revealed a range of different bias profiles among the newly synthesized compounds, namely, with regard to efficacy, potency, and GRK2 dependency, in which bias factors range from 1 to over 300 and activation from 15% to over 98% compared to quinpirole. These observations demonstrate that within bias, an even more precise tuning toward a particular profile is possible, which─in a general sense─could become an important aspect in future drug development. Docking studies enabled further insight into the role of the ECL2 and the EPB in the emergence of bias, thereby taking advantage of the diversity of functionally selective D4 agonists now available.
CRIS-Team Scopus Importer:2023-08-11

Fast and efficient 18F-labeling by [18F]fluorophenylazocarboxylic esters - Fehler, Stefanie; Maschauer, Simone; Höfling, Sarah; Bartuschat, Amelie; Tschammer, Nuska; Hübner, Harald; Gmeiner, Peter; Prante, Olaf; Heinrich, Markus (Chemistry - A European Journal, 2014)
Introduction of [(18) F]fluoride ion into the aromatic core of phenylazocarboxylic esters was achieved in only 30 seconds, with radiochemical yields of up to 95 % (85(±10) %). For labeling purposes, the resulting (18) F-substituted azoester can be further converted in radical-arylation reactions to give biaryls, or in substitutions at its carbonyl unit to produce azocarboxamides. Copyright © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
UnivIS-Import:2015-04-14:Pub.2014.nat.dchph.lphch.fastan

Fluoro-substituted phenylazocarboxamides: Dopaminergic behavior and N-arylating properties for irreversible binding - Bartuschat, Amelie; Schellhorn, Tamara; Hübner, Harald; Gmeiner, Peter; Heinrich, Markus (Bioorganic & Medicinal Chemistry, 2015)
UnivIS-Import:2015-04-14:Pub.2015.nat.dchph.lphch.fluoro

How the Structural elucidation of the natural product Stephanosporin led to new developments in aryl radical and medicinal chemistry - Fehler, Stefanie; Heinrich, Markus (Synlett, 2015)
The intent of this account is to provide a focused overview of recent developments in aryl radical chemistry, especially extensions and applications of the Meerwein arylation and the Gomberg-Bachmann reaction. Although most of the reactions and methods described were discovered on the basis of earlier findings made by our group or logically depend on newly discovered reactivities or mechanistic principles, the rapid evolution of radical chemistry can nevertheless be traced back to the behavior of the natural product stephanosporin, which is capable of liberating 2-chloro-4-nitrophenol via an aryl radical intermediate.
Keywords: arylations; diazonium compounds; Gomberg-Bachmann reactions; hydrazines; Meerwein reactions; radical reactions

Identification and Quantification of Resveratrol and Its Derivatives in Franconian Wines by Comprehensive Liquid Chromatography-Tandem Mass Spectrometry - Hoferer, Laura; Rodrigues Guimarães Abreu, Vera Lúcia; Graßl, Fabian; Fischer, Oliver; Heinrich, Markus; Gensberger-Reigl, Sabrina (ACS Food Science & Technology, 2023)
Resveratrol and its derivatives are valued compounds in foods such as wine. To date, their occurrence and concentrations in Franconian wines are not known. Thus, the present study investigated resveratrol and its derivatives in Franconian wines. First, comprehensive ultrahigh-performance liquid chromatography (UHPLC)-tandem mass spectrometry methods were applied to identify cis-/trans-resveratrol, cis-/trans-piceid, deoxyrhapontigenin, trans-piceatannol, and cis-/trans-astringin. Second, a sensitive UHPLC-scheduled multiple reaction monitoring method for absolute quantification of the major resveratrol derivatives was developed, validated, and applied to 19 Franconian wine samples. Recovery rates ranged between 95.0 and 109.3% and reproducibility between 2.6 and 10.3%. The limits of detection/quantification were between 0.01 and 0.08 μg/mL. The samples contained 0.07-2.61 μg/mL cis-resveratrol, 0.05-3.82 μg/mL trans-resveratrol, 0.24-9.01 μg/mL cis-piceid, and 0.25-8.30 μg/mL trans-piceid. Additionally, the concentrations of deoxyrhapontigenin (0.02-0.53 μg/mL), trans-piceatannol (0.05-1.35 μg/mL), and trans-astringin (0.04-0.67 μg/mL) were quantified.
CRIS-Team Scopus Importer:2023-07-07
Keywords: piceid; precursor ion scan; resveratrol; scheduled multiple reaction monitoring; stilbene derivatives; UHPLC−MS/MS; wine

Identification of novel inhibitors of the transcriptional coactivator MRTF-A for HCC therapy - Franz, Miriam; Wenisch, Pia; Wohlleben, Petra; Rupprecht, Laura; Chubanov, Vladimir; Gudermann, Thomas; Kyheröinen, Salla; Vartiainen, Maria Kristina; Heinrich, Markus; Mühlich, Susanne (Molecular Therapy Oncology, 2024)
Myocardin-related transcription factor A (MRTF-A) is a coactivator of serum response factor (SRF), which regulates the expression of genes involved in cell proliferation, migration, and differentiation and has been implicated in hepatocellular carcinoma (HCC) progression. We recently established inhibition of the transcriptional activity of MRTF-A by NS8593 as a novel therapeutic approach for HCC therapy. NS8593 is a negative gating modulator of the transient receptor potential cation channel TRPM7. In this report, we identify an aminobenzimidazole that is highly potent in inhibiting TRPM7 and its interaction with RhoA, leading to decreased SRF transcriptional activity and enhanced nuclear export of MRTF-A, as determined by fluorescence loss in photobleaching (FLIP). This resulted in reduced expression of the MRTF/SRF target genes transforming growth factor β1 (TGF-β1) and tetraspanin 5 (TSPAN5), senescence induction, and growth arrest in HCC cells. Replacement of the tetraline core by a 3-aminophenyl substructure yielded inhibitor 10 with higher potency than inhibitor 5, and further structural modifications yielded highly potent inhibitors of SRF activity, 14 and 16. Both compounds were capable of inhibiting cell proliferation and inducing senescence in HCC cells with improved efficacy compared to NS8593. These inhibitors represent valuable tools for understanding the molecular basis of drug development targeting TRPM7 and MRTFs.
CRIS-Team Scopus Importer:2024-11-08
Keywords: HCC; MKL1; MRTF; MT: Regular Issue; NS8593; RhoA; SK; SRF; TGF-ß1; TRPM7; TSPAN5

Illuminating Neuropeptide Y Y4 Receptor Binding: Fluorescent Cyclic Peptides with Subnanomolar Binding Affinity as Novel Molecular Tools - Gleixner, Jakob; Kopanchuk, Sergei; Grätz, Lukas; Tahk, Maris Johanna; Laasfeld, Tõnis; Veikšina, Santa; Höring, Carina; Gattor, Albert O.; Humphrys, Laura J.; Müller, Christoph; Archipowa, Nataliya; Köckenberger, Johannes; et al. (ACS Pharmacology & Translational Science, 2024)
The neuropeptide Y (NPY) Y4 receptor (Y4R), a member of the family of NPY receptors, is physiologically activated by the linear 36-amino acid peptide pancreatic polypeptide (PP). The Y4R is involved in the regulation of various biological processes, most importantly pancreatic secretion, gastrointestinal motility, and regulation of food intake. So far, Y4R binding affinities have been mostly studied in radiochemical binding assays. Except for a few fluorescently labeled PP derivatives, fluorescence-tagged Y4R ligands with high affinity have not been reported. Here, we introduce differently fluorescence-labeled (Sulfo-Cy5, Cy3B, Py-1, Py-5) Y4R ligands derived from recently reported cyclic hexapeptides showing picomolar Y4R binding affinity. With pKi values of 9.22-9.71 (radioligand competition binding assay), all fluorescent ligands (16-19) showed excellent Y4R affinity. Y4R saturation binding, binding kinetics, and competition binding with reference ligands were studied using different fluorescence-based methods: flow cytometry (Sulfo-Cy5, Cy3B, and Py-1 label), fluorescence anisotropy (Cy3B label), and NanoBRET (Cy3B label) binding assays. These experiments confirmed the high binding affinity to Y4R (equilibrium pKd: 9.02-9.9) and proved the applicability of the probes for fluorescence-based Y4R competition binding studies and imaging techniques such as single-receptor molecule tracking.
CRIS-Team Scopus Importer:2024-03-29
Keywords: binding assay; fluorescence microscopy; fluorescent ligand; neuropeptide Y; pancreatic polypeptide; Y

Ligand-Biased and Probe-Dependent Modulation of Chemokine Receptor CXCR3 Signaling by Negative Allosteric Modulators - Bernat, Viachaslau; Brox, Regine; Heinrich, Markus; Auberson, Yves P.; Tschammer, Nuska (ChemMedChem, 2015)
Over the last decade, functional selectivity (or ligand bias) has evolved from being a peculiar phenomenon to being recognized as an essential feature of synthetic ligands that target Gprotein-coupled receptors (GPCRs). The CXC chemokine receptor3 (CXCR3) is an outstanding platform to study various aspects of biased signaling, because nature itself uses functional selectivity to manipulate receptor signaling. At the same time, CXCR3 is an attractive therapeutic target in the treatment of autoimmune diseases and cancer. Herein we report the discovery of an 8-azaquinazolinone derivative (N-1-[3-(4-ethoxyphenyl)-4-oxo-3,4-dihydropyrido[2,3-d]pyrimidin-2-yl]ethyl-4-(4-fluorobutoxy)-N-[(1-methylpiperidin-4-yl)methyl]butanamide, 1b) that can inhibit CXC chemokine11 (CXCL11)-dependent Gprotein activation over β-arrestin recruitment with 187-fold selectivity. This compound also demonstrates probe-dependent activity, that is, it inhibits CXCL11- over CXCL10-mediated Gprotein activation with 12-fold selectivity. Together with a previously reported biased negative allosteric modulator from our group, the present study provides additional information on the molecular requirements for allosteric modulation of CXCR3. How amazing can 1b? The chemokine receptor CXCR3 is an outstanding platform to study various aspects of allosteric modulation. Herein we report the discovery of a small molecule (compound 1b) that can inhibit CXCL11-dependent Gprotein activation over β-arrestin recruitment with 187-fold selectivity. Compound 1b also demonstrates probe-dependent activity: it inhibits CXCL11- over CXCL10-mediated Gprotein activation with 12-fold selectivit
Keywords: Allosteric modulation; Chemokine receptor CXCR3; Ligand-biased signaling; Probe dependence

Markus R. Heinrich - Heinrich, Markus (Tetrahedron, 2016)

Medication safety in intravenous therapy: A compatibility study and analysis of reaction products of dihydralazine and metamizole - Koller, Anna Katharina; Fischer, Oliver; Krebs, Sabine; Heinrich, Markus; Dörje, Frank (Scientia Pharmaceutica, 2020)
The pharmacotherapy of critically ill patients is challenging due to the variety of drugs that have to be applied. As the majority of pharmaceuticals must be administered intravenously because of the critical condition of the patients, the compatibility of co-applied intravenous drugs is crucial for a safe and successful infusion therapy. Antihypertensive therapy was reported by health care professionals to be ineffective in association with concomitant application of dihydralazine and metamizole (dipyrone). As both drugs are administered in German intensive care units, we analyzed their compatibility, examined the mechanisms of underlying dihydralazine degradation, and identified reaction products of dihydralazine and metamizole. Binary combinations were prepared at the high and the low end of the nominal administration concentration. Validated high performance liquid chromatography/ultraviolet absorption (HPLC-UV) analysis was conducted to quantify drug amount and high performance liquid chromatography/mass spectrometry (HPLC-MS) was used to analyze degradation products. The combinations of dihydralazine and metamizole proved to be incompatible as dihydralazine concentration decreased immediately and considerably. Metamizole also slightly decreased over time. Specific degradation products of dihydralazine were identified and a degradation pathway was postulated. Our findings demonstrate that the intravenous co-administration of dihydralazine and metamizole should be strictly avoided due to the incompatibility of these two drugs.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Dihydralazine; HPLC-MS; HPLC-UV; Infusion therapy; Medication safety; Metamizole; Y-site compatibility

Microwave-assisted rapid one-pot synthesis of fused and non-fused indoles and 5-[18F]fluoroindoles from phenylazocarboxylates - Krüll, Jasmin; Hubert, Anja; Nebel, Natascha; Prante, Olaf; Heinrich, Markus (Chemistry - A European Journal, 2017)
Substituted indoles can be prepared from phenylazo-carboxylates through a rapid one-pot sequence featuring a microwave-assisted Fischer indole synthesis as key step. As the phenylazocarboxylates may beforehand be modified by mild nucleophilic aromatic substitution, including the introduction of [18F]fluoride, the overall strategy offers an attractive new access to 5-[18F]fluoroindoles.
EVALuna2:13873

Molecular mechanisms of biased and probe-dependent signaling at CXC-motif chemokine receptor CXCR3 induced by negative allosteric modulators - Brox, Regine; Milanos, Lampros; Saleh, Noureldin; Baumeister, Paul; Buschauer, Armin; Hofmann, Dagmar; Heinrich, Markus; Clark, Timothy; Tschammer, Nuska (Molecular Pharmacology, 2018)

N-Alkylaminoferrocene-Based Prodrugs Targeting Mitochondria of Cancer Cells - Reshetnikov, Viktor; Özkan, Hülya; Daum, Steffen; Janko, Christina; Alexiou, Christoph; Sauer, Caroline; Heinrich, Markus; Mokhir, Andriy (Molecules, 2020)
Intracellular concentration of reactive oxygen species (e.g., H2O2) in cancer cells is elevated over 10-fold as compared to normal cells. This feature has been used by us and several other research groups to design cancer specific prodrugs, for example, N-alkylaminoferrocene (NAAF)-based prodrugs. Further improvement of the efficacy of these prodrugs can be achieved by their targeting to intracellular organelles containing elevated reactive oxygen species (ROS) amounts. For example, we have previously demonstrated that lysosome-targeted NAAF-prodrugs exhibit higher anticancer activity in cell cultures, in primary cells and in vivo (Angew. Chem. Int. Ed. 2017, 56, 15545). Mitochondrion is an organelle, where electrons can leak from the respiratory chain. These electrons can combine with O2, generating O2-• that is followed by dismutation with the formation of H2O2. Thus, ROS can be generated in excess in mitochondria and targeting of ROS-sensitive prodrugs to these organelles could be a sensible possibility for enhancing their efficacy. We have previously reported on NAAF-prodrugs, which after their activation in cells, are accumulated in mitochondria (Angew. Chem. Int. Ed. 2018, 57, 11943). Now we prepared two hybrid NAAF-prodrugs directly accumulated in mitochondria and activated in these organelles. We studied their anticancer activity and mode of action. Based on these data, we concluded that ROS produced by mitochondria is not available in sufficient quantities for activation of the ROS-responsive prodrugs. The reason for this can be efficient scavenging of ROS by antioxidants. Our data are important for the understanding of the mechanism of action of ROS-activatable prodrugs and will facilitate their further development.
CRIS-Team Scopus Importer:2020-06-16
Keywords: cancer; mitochondrion; N-alkylaminoferrocene; prodrug; reactive oxygen species

New Biomarkers for Renal Transporter-Mediated Drug–Drug Interactions: Metabolomic Effects of Cimetidine, Probenecid, Verapamil, and Rifampin in Humans - Geßner, Arne; König, Jörg; Wenisch, Pia; Heinrich, Markus; Stopfer, Peter; Fromm, Martin; Müller, Fabian (Clinical Pharmacology & Therapeutics, 2024)
The inhibition of renal transport proteins organic cation transporter 2 (OCT2), multidrug and toxin extrusion proteins (MATE1, MATE2-K), and organic anion transporters (OAT1, OAT3) causes clinically relevant drug–drug interactions (DDI). Endogenous biomarkers could be used to improve risk prediction of such renal DDIs. While a number of biomarkers for renal DDIs have been described so far, multiple criteria for valid biomarkers have frequently not been investigated, for example, specificity, metabolism, or food effects. Therefore, there is a need for novel biomarkers of renal DDIs. Here, we investigated the global metabolomic effects following the administration of two classical inhibitors of renal transport proteins [cimetidine (OCT2/MATEs), probenecid (OATs)] in human plasma and urine of healthy volunteers. Additionally, we investigated metabolomic effects of two inhibitors of other transporters [verapamil (P-glycoprotein), rifampin (organic anion transporting polypeptides)] as controls. This analysis shows that both cimetidine and probenecid affect compounds involved in caffeine metabolism, carnitines, and sulfates. Hierarchical cluster analysis of the effects of all four inhibitors on endogenous compounds identified multiple promising new sensitive and specific biomarker candidates for OCT2/MATE- or OAT-mediated DDIs. For OCT2/MATEs, 5-amino valeric acid betaine (median log2-fold change of estimated renal elimination: −3.62) presented itself as a promising candidate. For OATs, estimated renal elimination of 7-methyluric acid and cinnamoylglycine (median log2-fold changes −3.10 and −1.92, respectively) was both sensitive and specific. This study provides comprehensive information on metabolomic effects of transport protein inhibition in humans and identifies putative new sensitive and specific biomarkers for renal transporter-mediated DDIs.
CRIS-Team Scopus Importer:2024-08-23

Organic chemistry—more radical than ever before - Heinrich, Markus (Tetrahedron, 2016)

Oxidative Formation of Disulfide Bonds by a Chemiluminescent 1,2-Dioxetane under Mild Conditions - Sauer, Caroline; Köckenberger, Johannes; Heinrich, Markus (Journal of Organic Chemistry, 2020)
The oxidation of alkyl thiols to disulfides has been achieved under mild conditions using a chemiluminescent 1,2-dioxetane as a stoichiometric oxidant. Besides the mild and biocompatible reaction conditions, this approach offers the possibility to monitor the presence of thiols through oxidation and chemiluminescence of the remaining dioxetane.
CRIS-Team WoS Importer:2020-08-07

PH-Dependent Conformational Switching of Amide Bonds from Full trans to Full cis and Vice Versa - Thurston, Ryan; Zantop, Viviane; Park, Kristen Sodam; Maid, Harald; Seitz, Anke; Heinrich, Markus (Organic Letters, 2022)
Strategies enabling the pH-dependent conformational switching of amide bonds from trans to cis, and vice versa, are yet limited in the sense that, in a suitable pH range, one rotamer may be stabilized to a large extent while the complementary pH range only leads to a mixture of isomers. By exploiting the effects of steric demand and the interaction of the amide carbonyl with a positive charge, we herein present the first examples for reversible pH-dependent switching from full trans to full cis.
CRIS-Team Scopus Importer:2022-06-03

Radical Arylation of Anilines and Pyrroles via Aryldiazotates - Hofmann, Josefa; Gans, Eva; Clark, Timothy; Heinrich, Markus (Chemistry - A European Journal, 2017)
The radical arylation of anilines and pyrroles can be achieved under transition-metal- and catalyst-free conditions by using aryldiazotates in strongly alkaline aqueous solutions. The aryldiazotates act as protected diazonium ions, which do not undergo azo coupling with electron-rich aromatic substrates, but can still serve as an aryl radical source at slightly elevated temperatures. Based on an improved preparation of aryldiazotates in aqueous solution, homolytic aromatic substitutions of anilines and pyrroles were conducted with good overall yields and high regioselectivity. Moreover, DFT calculations provided further mechanistic insights.

Radical arylation of tyrosine and its application in the synthesis of a highly selective neurotensin receptor 2 ligand - Pratsch, Gerald; Unfried, Johannes F.; Einsiedel, Jürgen; Plomer, Manuel; Hübner, Harald; Gmeiner, Peter; Heinrich, Markus (Organic & Biomolecular Chemistry, 2011)
A small library of Fmoc-protected 3-arylated tyrosines was created by radical arylation. The new building blocks were successfully applied in the synthesis of two novel neurotensin receptor ligands. Both isomers showed high affinity for the human NTS2 receptor with K values in the nanomolar range. Interestingly, subtype selectivity strongly depends on the configuration of the peptide in position 11. Isomer (11R)-3 displayed an excellent preference for NTS2 compared to NTS1. © 2011 The Royal Society of Chemistry.

Radical arylation of tyrosine residues in peptides - Fehler, Stefanie; Pratsch, Gerald; Östreicher, Christiane; Fürst, Michael; Pischetsrieder, Monika; Heinrich, Markus (Tetrahedron, 2016)
The radical arylation of the phenolic side chain of tyrosine in peptides was investigated. Aryl radicals were generated from aryldiazonium salts using titanium(III) chloride as stoichiometric reductant. Due to the high selectivity with which 3-aryltyrosine derivatives were formed, this reaction type represents a new strategy for the direct functionalization of peptides.
Keywords: Arylation; Diazonium; Peptide; Radical reaction; Tyrosine

Radical Carbofluorination of Alkenes with Arylhydrazines and Selectfluor: Additives, Mechanistic Pathways, and Polar Effects - Pirzer, Anna; Alvarez, Eva-Maria; Friedrich, Heike; Heinrich, Markus (Chemistry - A European Journal, 2019)
Radical carbofluorination reactions starting from arylhydrazines and nonactivated alkenes, in which the C-F bond is formed through the use of Selectfluor, can be improved through the addition of anisole. Because direct trapping products could be detected only in trace amounts, anisole does primarily act as a reversible scavenger for the highly reactive ammonium radical dication released from Selectfluor in the C-F bond-forming step. As shown for three diverse substitution patterns, the main role of anisole is to prevent, or at least reduce, the undesired addition of the ammonium radical dication to the alkene, which in turn leads to an unfavorable consumption of the arylhydrazine-derived precursors required for carbofluorination. Moreover, besides the remarkable polar effects in radical trapping, this study shows that the Selectfluor-derived nitrogen-centered radical dication may add directly to alkenes, which has not been described so far.
CRIS-Team WoS Importer:2019-03-06

Recent Advances in Meerwein Arylation Chemistry - Kindt, Stephanie; Heinrich, Markus (Synthesis (Germany), 2016)
The Meerwein arylation has recently received much attention and a variety of new variants have been developed. Advances include new sources for aryl radicals, new radical scavengers, as well as improved reaction conditions. This short review summarizes important developments that make this radical-type reaction an even more powerful tool for the diverse functionalization of alkenes. 1 Introduction 2 Meerwein Arylations 2.1 Carboarylation 2.2 Carboamination 2.3 Carbooxygenation 2.4 Carbothiolation 2.5 Carbofluorination 3 Summary.
Keywords: alkene; diazonium; Meerwein arylation; photocatalysis; radical reactions; radical-polar crossover

Recent developments in intermolecular radical arylations of arenes and heteroarenes - Hofmann, Josefa; Heinrich, Markus (Tetrahedron Letters, 2016)
This short review gives an overview over recent developments in the field of intermolecular radical arylations of arenes and heteroarenes. Transformations of this type are formally comparable to C–H activation reactions and more simple starting materials can thus be used than in most organometallic cross-coupling procedures.
Keywords: Arylation; Arylhydrazines; Biaryls; Diazonium salts; Radical reactions

Regioselective Radical Arylation of 3-Hydroxypyridines - Fürst, Michael; Bock, Leonard; Heinrich, Markus (Journal of Organic Chemistry, 2016)
The titanium(III)-mediated radical arylation of 3-hydroxypyridines was found to proceed with high regioselectivity for the 2-position. Using aryldiazonium chlorides, which were prepared from the corresponding anilines, as aryl radical sources, a range of 3-hydroxy-2-phenylpyridines were obtained in moderate to good yields under simple reaction conditions. Reactions of ortho-carboxylic ester substituted phenyldiazonium salts directly provided tricyclic benzopyranopyridinones.

Regiospecific Introduction of Halogens on the 2-Aminobiphenyl Subunit Leading to Highly Potent and Selective M3 Muscarinic Acetylcholine Receptor Antagonists and Weak Inverse Agonists - Fischer, Oliver; Hofmann, Josefa; Rampp, Hannelore; Kaindl, Jonas; Pratsch, Gerald; Bartuschat, Amelie; Taudte, Verena; Fromm, Martin; Hübner, Harald; Gmeiner, Peter; Heinrich, Markus (Journal of Medicinal Chemistry, 2020)
Muscarinic M-3 receptor antagonists and inverse agonists displaying high affinity and subtype selectivity over the antitarget M-2 are valuable pharmacological tools and may enable improved treatment of chronic obstructive pulmonary disease (COPD), asthma, or urinary incontinence. On the basis of known M-3 antagonists comprising a piperidine or quinuclidine unit attached to a biphenyl carbamate, S-fluoro substitution was responsible for M-3 subtype selectivity over M-2, while 3'-chloro substitution substantially increased affinity through a sigma-hole interaction. Resultantly, two piperidinyl- and two quinuclidinium-substituted biphenyl carbamates OFH243 (13n), OFH244 (13m), OFH3911 (14n), and OFH3912 (14m) were discovered, which display two-digit picomolar affinities with K-i values from 0.069 to 0.084 nM, as well as high selectivity over the M-2 subtype (46- to 68-fold). While weak inverse agonistic properties were determined for the biphenyl carbamates 13m and 13n, neutral antagonism was observed for 14m and 14n and tiotropium under identical assay conditions.
CRIS-Team WoS Importer:2020-05-15

Selectfluor-Mediated Chlorination and Fluorination of Arenes: Late-Stage Functionalization of APIs and Its Biological Effects - Gradl, Susanne; Zantop, Viviane; Gmeiner, Peter; Hübner, Harald; Heinrich, Markus (ChemMedChem, 2023)
By using active pharmaceutical ingredients (APIs) previously recovered from expired drugs, it is shown that Selectfluor can act as a reagent for operationally simple late-stage fluorination and chlorination of electron-rich arenes under mild reaction conditions. As shown in mechanistic experiments, aromatic fluorination thereby competes with chlorine-for-fluorine exchange on Selectfluor and subsequent aromatic chlorination, whereat the chloride ions may either be provided by the hydrochloride salt of the respective API or by triethylammonium chloride. Biological testing of the fluorinated or chlorinated APIs at adrenergic, dopaminergic, muscarinergic, opioid or serotoninergic receptors demonstrated that improved binding affinities can be achieved via this straightforward strategy.
CRIS-Team Scopus Importer:2023-05-19
Keywords: active pharmaceutical ingredients; chlorination; fluorination; screening; Selectfluor

Selective Functionalization of Graphene at Defect-Activated Sites by Arylazocarboxylic tert-Butyl Esters - Halbig, Christian E.; Lasch, Roman; Krüll, Jasmin; Pirzer, Anna; Wang, Zhenping; Kirchhof, Jan N.; Bolotin, Kirill I.; Heinrich, Markus; Eigler, Siegfried (Angewandte Chemie International Edition, 2019)
The development of versatile functionalization concepts for graphene is currently in the focus of research. Upon oxo-functionalization of graphite, the full surface of graphene becomes accessible for C-C bond formation to introduce out-of-plane functionality. Herein, we present the arylation of graphene with arylazocarboxylic tert-butyl esters, which generates aryl radicals after activation with an acid. Surprisingly, the degree of functionalization is related to the concentration of lattice vacancy defects in the graphene material. Consequently, graphene materials that are free from lattice defects are not reactive. The reaction can be applied to graphene dispersed in solvents and leads to bitopic functionalization as well as monotopic functionalization when the graphene is deposited on surfaces. As the arylazocarboxylic tert-butyl ester moiety can be attached to various molecules, the presented method paves the way to functional graphene derivatives, with the density of defects determining the degree of functionalization.
CRIS-Team WoS Importer:2019-03-20

Sequential Cleavage of Lignin Systems by Nitrogen Monoxide and Hydrazine - Hofmann, Laura; Hofmann, Dagmar; Prusko, Lea; Altmann, Lisa-Marie; Heinrich, Markus (dvanced Synthesis & Catalysis, 2020)
The cleavage of representative lignin systems has been achieved in a metal-free two-step sequence first employing nitrogen monoxide for oxidation followed by hydrazine for reductive C−O bond scission. In combining nitrogen monoxide and lignin, the newly developed valorization strategy shows the particular feature of starting from two waste materials, and it further exploits the attractive conditions of a Wolff-Kishner reduction for C−O bond cleavage for the first time. (Figure presented.).
CRIS-Team Scopus Importer:2020-03-31
Keywords: Depolymerization; Hydrazine; Lignin; Nitrogen oxides; Pyrazole

Shifted Selectivity in Protonation Enables the Mild Deuteration of Arenes Through Catalytic Amounts of Bronsted Acids in Deuterated Methanol - Fischer, Oliver; Hubert, Anja; Heinrich, Markus (Journal of Organic Chemistry, 2020)
Taking advantage of the "differentiating effect" of the solvent methanol, deuterations of electron-rich aromatic systems can be carried out under mild acid catalysis and thus under far milder conditions than known so far. The exceptional functional group tolerance observed under the optimized conditions, which even includes highly acid-labile groups, results from a hitherto unexploited shifted selectivity in protonation, and enabled simple and straightforward access to complex deuterium-labeled compounds.
CRIS-Team WoS Importer:2020-10-23

Strongly Directing Substituents in the Radical Arylation of Substituted Benzenes - Hofmann, Josefa; Clark, Timothy; Heinrich, Markus (Journal of Organic Chemistry, 2016)
Although general interest in radical arylation reactions has grown rapidly in recent years, poor regioselectivities and the need to use a large excess of the radical-accepting arene have hindered their application to substituted benzenes. We now describe experimental and computational investigations into the substituent effects that lead to regioselective addition based on the recent discovery of anilines as outstanding substrates for radical arylations.

Structure-guided development of selective M3 muscarinic acetylcholine receptor antagonists - Liu, Hongtao; Hofmann, Josefa; Fish, Inbar; Schaake, Benjamin; Eitel, Katrin; Bartuschat, Amelie; Kaindl, Jonas; Rampp, Hannelore; Banerjee, Ashutosh; Hübner, Harald; Clark, Mary J.; Vincent, Sandra G.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2018)
Keywords: Muscarinic receptor; Subtype selectivity; G protein-coupled receptor; Drug design; Crystal structure

Synthesis and biological evaluation of biphenyl amides that modulate the US28 receptor - Kralj, Ana; Kurt, Elif; Tschammer, Nuska; Heinrich, Markus (ChemMedChem, 2014)
To prepare and biologically evaluate 38 new potential US28 allosteric modulators, we employed a straightforward synthetic route involving radical arylation. The study was based on a former lead structure but with the dihydroisoquinolinone moiety replaced by substituted biphenyls. The investigation of structure-activity relationships among the new biphenyl-derived ligands led to a preliminary pharmacophore model and the discovery of four promising candidates with full inverse agonist properties. Hit HCMV GPCRs ASAP! Employing a straightforward synthetic access involving radical arylation, 38 new potential US28 allosteric modulators were prepared and biologically evaluated. The investigation of structure-activity relationships among the new biphenyl-derived ligands led to a consistent model and the discovery of four promising candidates with full inverse agonist properties. Copyright © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: amides; biphenyls; human cytomegalovirus; inverse agonism; US28 receptor

Synthesis and evaluation of fluoro substituted pyridinylcarboxamides and their phenylazo analogues for potential dopamine D3 receptor PET imaging - Nebel, Natascha; Maschauer, Simone; Bartuschat, Amelie; Fehler, Stefanie; Hübner, Harald; Gmeiner, Peter; Kuwert, Torsten; Heinrich, Markus; Prante, Olaf; Hocke, Carsten (Bioorganic & Medicinal Chemistry Letters, 2014)
A series of fluoro substituted pyridinylcarboxamides and their phenylazo analogues with high affinity and selectivity for the dopamine D3 receptor was synthesized by the use of 6-fluoropyridine-3-carbonyl chloride (1) and fluorophenylazocarboxylic ester (2). Several of these compounds (9a-e and 10a-h) have been evaluated in vitro, among which 9b, 10a, 10c and 10d proved to have at least single-digit nanomolar affinity for D3. They also exhibit considerable selectivity over the other dopamine receptor subtypes and noteworthy selectivity over the structurally related serotonin receptor subtypes 5-HT1A and 5-HT2, offering potential radiotracers for positron emission tomography.
UnivIS-Import:2015-04-14:Pub.2014.nat.dchph.lphch.synthe_8
Keywords: Azoester; D3 receptor; Dopamine; Fluorine; Fluoroarylation; PET

Synthesis, biological evaluation and radiolabelling by 18F- fluoroarylation of a dopamine D3-selective ligand as prospective imaging probe for PET - Höfling, Sarah; Maschauer, Simone; Hübner, Harald; Gmeiner, Peter; Wester, H. -J.; Prante, Olaf; Heinrich, Markus (Bioorganic & Medicinal Chemistry Letters, 2010)
Radical F-fluoroarylation with fluorine-18-labelled arenediazonium chlorides has been successfully applied to the radiochemical synthesis of the dopamine D-selective ligand SH 317 ([ F]8). SH 317 has been evaluated as a new PET ligand candidate by in vivo experiments. © 2010 Elsevier Ltd. All rights reserved.

Synthesis, Characterization, and Application of Muscarinergic M-3 Receptor Ligands Linked to Fluorescent Dyes - Köckenberger, Johannes; Fischer, Oliver; Konopa, Andreas; Bergwinkl, Sebastian; Mühlich, Susanne; Gmeiner, Peter; Kutta, Roger Jan; Hübner, Harald; Keller, Max; Heinrich, Markus (Journal of Medicinal Chemistry, 2022)
Through the linkage of two muscarinergic M-3 receptor ligands to fluorescent tetramethylrhodamine- and cyanine-S-type dyes, two novel tool compounds, OFH5503 and OFH611, have been developed. Based on the suitable binding properties and kinetics related to the M-3 subtype, both ligand-dye conjugates were found to be useful tools to determine binding affinities via flow cytometric measurements. In addition, confocal microscopy underlined the comparably low unspecific binding and the applicability for studying M-3 receptor expression in cells. Along with the proven usefulness regarding studies on the M-3, subtype, the conjugates OFH5503 and OFH611 could, due to their high affinity to the M-1 receptor, evolve as even more versatile tools in the field of research on muscarinergic receptors.
CRIS-Team WoS Importer:2023-01-06

Synthesis of 2-(Chlorodifluoromethyl)indoles for Nucleophilic Halogen Exchange with [18F]Fluoride - Bock, Leonard; Schultheiss, Stefanie K.; Maschauer, Simone; Lasch, Roman; Gradl, Susanne; Prante, Olaf; Zard, Samir Z.; Heinrich, Markus (European Journal of Organic Chemistry, 2021)
The synthesis of 2-[18F]trifluoromethylated indoles from the corresponding chlorodifluoromethyl precursors was found to proceed under milder conditions when compared to known metal-free nucleophilic exchange reactions with [18F]fluoride on chlorodifluoro-methyl arenes. A key element in the reaction course is – most likely – a favorable elimination-addition mechanism on the 2-methyl position of the indole. Given the increasing interest in 18F-labelled compounds, this single step labeling methodology nicely complements the so far existing routes to 2-[18F]trifluoromethylated indoles.
CRIS-Team Scopus Importer:2021-12-24
Keywords: Fluorine; Indoles; Nucleophilic substitution; Radical reactions; Radiochemistry

Synthesis of dibenzo[c,e][1,2]diazocines-a new group of eight-membered cyclic azo compounds - Nokubi, Tomomi; Kindt, Stephanie; Clark, Timothy; Kamimura, Akio; Heinrich, Markus (Tetrahedron Letters, 2015)
Despite of a remarkable ring strain hitherto unknown dibenzo[c,e][1,2]diazocines 3 could be prepared from readily available azo compounds 4 under mild Ullmann-type reaction conditions. The obtained stereoisomers of the new heterocycles 3 were structurally assigned by 2D NMR experiments and DFT calculations. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Radical reactions; Azo compounds; Ullmann coupling; Diazocines; Heterocycles

Synthesis of Fmoc- and Boc-Protected (2S,5S)- and (2R,5R)-5-Aminomethylprolines - Bartuschat, Amelie; Hegmann, Nina; Heinrich, Markus (Synthesis-Stuttgart, 2019)
The proline derivatives (2S, 5S) dmamPro, (2S, 5S) N-Boc-amPro and (2R, 5R) dmamPro are useful building blocks for peptides since they allow conformational fixation of peptidyl-CO-N-prolyl bonds in the unusual cis conformation. The stereoselective syntheses of these dimethylaminomethyl- prolines is achieved from literature-known precursors with overall yields of 23% [over 8 steps for (2S, 5S) dmamPro], 33% [over 9 steps for (2S, 5S) N-Boc-amPro] and 12% [over 8 steps for (2R, 5R) dmamPro]. The applicability of (2S, 5S) N-Boc-amPro in peptide synthesis is demonstrated through the preparation of an Fmoc-Val-amPro- OMe dipeptide.
CRIS-Team WoS Importer:2019-03-06

Synthesis, Radiosynthesis and Biological Evaluation of Buprenorphine-Derived Phenylazocarboxamides as Novel mu-Opioid Receptor Ligands - Krüll, Jasmin; Fehler, Stefanie; Hofmann, Laura; Nebel, Natascha; Maschauer, Simone; Prante, Olaf; Gmeiner, Peter; Lanig, Harald; Hübner, Harald; Heinrich, Markus (ChemMedChem, 2020)
Targeted structural modifications have led to a novel type of buprenorphine-derived opioid receptor ligand displaying an improved selectivity profile for the mu-OR subtype. On this basis, it is shown that phenylazocarboxamides may serve as useful bioisosteric replacements for the widely occurring cinnamide units, without loss of OR binding affinity or subtype selectivity. This study further includes functional experiments pointing to weak partial agonist properties of the novel mu-OR ligands, as well as docking and metabolism experiments. Finally, the unique bifunctional character of phenylazocarboxylates, herein serving as precursors for the azocarboxamide subunit, was exploited to demonstrate the accessibility of an F-18-fluorinated analogue.
Keywords: azo compounds; bioisosters; buprenorphine; opioid receptors; radiosynthesis

Synthetic Route to Phenyl Diazenes and Pyridazinium Salts from Phenylazosulfonates - Gradl, Susanne; Köckenberger, Johannes; Oppl, Janina; Schiller, Martin; Heinrich, Markus (Journal of Organic Chemistry, 2021)
The synthesis of pyridazinium salts was achieved from readily available phenylazosulfonates in a single reaction step. The reaction proceeds via the formation of short-lived phenyldiazenes, which-owing to the strongly acidic conditions-are partially protonated. The phenyldiazenes then undergo a rapid cycloaddition to furans to give pyridazinium salts via elimination of water. The fact that the pyridazinium synthesis shows a low sensitivity toward oxygen, although phenyldiazenes occur as intermediates, can be explained by the very fast cycloaddition step and the partial protonation of the phenyldiazene.
CRIS-Team Scopus Importer:2021-06-04

Thermally Induced Carbohydroxylation of Styrenes with Aryldiazonium Salts - Kindt, Stephanie; Wicht, Karina; Heinrich, Markus (Angewandte Chemie International Edition, 2016)
The radical carbohydroxylation of styrenes with aryldiazonium salts has been achieved under mild thermal conditions. A broad range of aryldiazonium salts was tolerated, and the reaction principle based on a radical–polar crossover mechanism could be extended to carboetherification as well as to a two-step, metal-free variant of the Meerwein arylation leading to stilbenes.
Keywords: carbohydroxylation; diazonium ions; Meerwein arylation; radical reactions; styrene

Tunable Composition of Mixed Self-Assembled Shell-by-Shell Structures on Nanoparticle Surfaces - Eigen, Andreas; Stiegler, Lisa; Gradl, Susanne; Schneider, Vanessa; Wedler, Vincent; Gaß, Henrik; Müller, Lukas; Sarcletti, Marco; Heinrich, Markus; Hirsch, Andreas; Halik, Marcus (Advanced Materials Interfaces, 2022)
The formation of mixed shell-by-shell (SbS) systems with tunable shell compositions is demonstrated by using molecular self-assembly driven by chemical recognition motifs. Aluminum oxide nanoparticles (AlOx-NPs) act as template surface for a self-assembled monolayer (SAM) of either partially fluorinated fluoroalkyl or alkyl chained phosphonic acid derivatives or defined stoichiometric mixtures of those. By providing an equimolar mixture of corresponding fluoroalkyl and alkyl-chained amphiphiles in water, the stoichiometry of underlaying mixed SAM on the NP-surface preferentially directs the composition of the secondary self-assembly. The composition of the shell-by-shell assemblies is studied by high performance liquid chromatography and fluorescence spectroscopy. The concept allows the formation of NP-templated vesicle-like bilayer structures, even consisting of orthogonal chain structures in tunable composition driven by chemical recognition and hydrophobic segregation.
Created from Fastlane, Scopus look-up
Keywords: hydro-; fluoro-; lipophilic/phobic; nanoparticles; self-assembly; shell-by-shell architectures; surface chemistry

Tuning the Polarity of Antibiotic-Cy5 Conjugates Enables Highly Selective Labeling of Binding Sites - Graßl, Fabian; Konrad, Maike; Krüll, Jasmin; Pezerovic, Azra; Zähnle, Leon; Burkovski, Andreas; Heinrich, Markus (Chemistry - A European Journal, 2023)
Multidrug-resistant bacteria pose a major threat to global health, even as newly introduced antibiotics continue to lose their therapeutic value. Against this background, deeper insights into bacterial interaction with antibiotic drugs are urgently required, whereas fluorescently labeled drug conjugates can serve as highly valuable tools. Herein, the preparation and biological evaluation of 13 new fluorescent antibiotic-Cy5 dye conjugates is described, in which the tuning of the polarity of the Cy5 dye proved to be a key element to achieve highly favorable properties for various fields of application.
CRIS-Team Scopus Importer:2023-07-28
Keywords: antibiotics; cyanines; dye conjugates; fluorescence; microscopy

Twofold carbon-carbon bond formation by intra- and intermolecular radical reactions of aryl diazonium salts - Jasch, Hannelore; Landais, Yannick; Heinrich, Markus (Chemistry - A European Journal, 2013)
Cascade reactions: A variety of novel cascade reactions can be performed when the known and well-studied radical 5- or 6-exo-cyclization of an aryl diazonium salt is conducted in the presence of alkenes and further optional scavengers (see scheme). Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: aryl radicals; carbon-carbon bond formation; cascade reactions; cyclization; radical reactions

Ullmanns Encyclopedia of Industrial Chemistry: Antiparasitics (P) - Pirzer, Anna; Fürst, Michael; Heinrich, Markus (Ullmanns Encyclopedia of Industrial Chemistry, 2018)

Visible light-mediated catalyst-free radical arylations using arenediazonium salts - Wenisch, Pia; Kuschow, Meret; Heinrich, Markus (Arkivoc, 2024)
Radical arylation reactions based on arenediazonium salts have a long history in organic chemistry. While early methods to generate aryl radicals relied on metals, metal catalysts or basic conditions, more recent developments focused on the use of photoredox catalysts. As such catalysts are nevertheless additives, and they thus have to be separated during work-up, an even more attractive option is to exploit charge-transfer complexes between the arenediazonium ion and its substrate to enable aryl radical generation under visible light irradiation. In this review, we summarize recent developments in this particular field of visible light-promoted, additive-free radical arylation reactions.
CRIS-Team Scopus Importer:2023-12-22
Keywords: Arenediazonium; arylation; charge transfer; photochemistry; radical reactions

Visible-Light-Mediated Radical Arylations Using a Fluorescein- Derived Diazonium Salt: Reactions Proceeding via an Intramolecular Forth and Back Electron Transfer - Diesendorf, Nina; Wenisch, Pia; Oppl, Janina; Heinrich, Markus (Organic Letters, 2023)
Functionalizations of arenes and alkenes via additive-free radical reactions using highly photosensitive, fluorescein-derived diazonium salts are described. The particular properties of the diazonium salts enable unique Meerwein-type carbohydroxylations of non-activated alkenes, which can be rationalized by a reaction mechanism involving forth and back electron transfer from and to the xanthene subunit of the fluorescein moiety.
CRIS-Team WoS Importer:2023-01-27

Visible Light Promoted, Catalyst-Free Radical Carbohydroxylation and Carboetherification under Mild Biomimetic Conditions - Altmann, Lisa-Marie; Zantop, Viviane; Wenisch, Pia; Diesendorf, Nina; Heinrich, Markus (Chemistry - A European Journal, 2021)
Metal and catalyst-free carbohydroxylations and carboetherifications at room temperature have been achieved by a combination of beneficial factors including high aryl diazonium concentration and visible light irradiation. The acceleration of the reaction by visible light irradiation is particularly remarkable against the background that neither the aryldiazonium salt nor the alkene show absorptions in the respective range of wavelength. These observations point to weak charge transfer interactions between diazonium salt and alkene, which are nevertheless able to considerably influence the reaction course. As highly promising perspective, many more aryldiazonium-based radical arylations might benefit from simple light irradiation without requiring a photocatalyst or particular additive.
CRIS-Team Scopus Importer:2021-02-05
Keywords: arylation; biomimetics; diazonium; Meerwein; styrene